Pengaruh Fear Of Failure terhadap Prokrastinasi Akademik Siswa MTS Nurul Ulum Welahan - Endah Tri Puspita Arum; Venty Venty; Farikha Wahyu Lestari (Scidacplus, 2026)
Academic procrastination is a common problem among students and may negatively affect their learning process and academic achievement. One of the psychological factors associated with this behavior is fear of failure, which reflects students' concerns about experiencing failure and receiving negative evaluations from others. This study aimed to examine the effect of fear of failure on academic procrastination among students at MTs Nurul Ulum Welahan. A quantitative approach was employed, and the data were analyzed using simple linear regression. The study involved 111 students selected using a total sampling technique. Data were collected through the Fear of Failure Scale and the Academic Procrastination Scale, both of which met the validity and reliability requirements. The results showed that fear of failure had a positive and significant effect on academic procrastination (B = 0.604; p = 0.000). In addition, fear of failure explained 21.7% of the variance in academic procrastination, while the remaining 78.3% was influenced by other factors not examined in this study. These findings indicate that reducing students' fear of failure is important to help minimize academic procrastination through appropriate school counseling services